Комп’ютерне моделювання криволінійних поверхонь на основі масиву точок - Холодняк, Юлія Володимирівна; Гавриленко, Євген Андрійович; Мірошниченко, Микола Юрійович; Kholodniak, Yuliia; Havrylenko, Yevhen; Miroschnychenko, Mykola (Запоріжжя : ТДАТУ, 2022)
UA: Розроблено метод формування каркасів поверхонь, заданих масивом точок. З вихідного масиву точок виділяються підмножини – точкові ряди, на основі яких формуються лінійні елементи каркасу поверхні. Каркас формується на основі сімейства напрямних та сімейства твірних кривих ліній. На даний момент найбільш актуальним є завдання формування каркасів, що задають поверхню, функціональне призначення яких – взаємодія із середовищем. Запропоновано способи формування лінійних елементів каркасу із забезпеченням регулярної зміни геометричних характеристик вздовж кривої при контролі виникнення особливих точок. Зазначені властивості елементів каркасу забезпечують необхідні властивості поверхні. Розроблений метод випробуваний при моделюванні функціональних поверхонь, що обмежують міжлопатковий канал робочого колеса турбокомпресора. Випробування турбокомпресора, робочі поверхні якого виготовлені на основі запропонованого методу, показало збільшення продуктивності на 2,5%. EN: The method of forming linear elements of surface frameworks, the functional purpose of which is to interact with the environment based on an array of points is proposed in this article. A method of analyzing the original point series has been developed, which allows you to determine areas that can be interpolated by a monotone curved line. The analysis allows you to form a curve for monotonous sections within the area of their possible location. The dimensions of the area allow us to estimate the error with which the formed curve is a curve belonging to the surface. Methods of forming flat and spatial contours have been developed, which with a given accuracy represent curved lines with given geometric properties: a regular change in the values of curvature and twist with a minimum number of individual points: points of inflection, points of change in the direction of growth of values of curvature and twist, points of changes in the course of the curve. The obtained contours are used in the SolidWorks CAD system as generating and guiding curves when forming a surface model using the "Surface by intersections" function. The developed method was tested during modeling of functional surfaces limiting the turbocharger impeller. The quality of the formation of the impeller model is evaluated using: gas-dynamic analysis of the flow in the interblade channel, which is limited by the surfaces of the impeller and the turbocharger cover; testing of the finished product, equipped with an impeller, which is manufactured using our method, on a "closed circuit" type stand. Bench tests and gas-dynamic analysis showed that the manufacturing of the impeller surfaces based on the developed method improved their dynamic qualities compared to the original product. The prospect of further development of the method is to expand the scope of its possible application. Adaptation of the method to the solution of various tasks can be ensured by increasing the number of conditions that can be imposed on the curve. Such conditions can be an increase in the number of geometric characteristics, the values of which are assigned at the starting points, the formation of a curve of a given length, ensuring the touching of a curve with lines or surfaces, and others.
Computer simulation of curvilinear surfaces based on an array of points
Холодняк Ю. В., Гавриленко Є. А., Мірошниченко М. Ю. Комп’ютерне моделювання криволінійних поверхонь на основі масиву точок. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ, 2022. Вип. 12. том 3. C. 319-334.
Keywords: масив точок; каркас поверхні; напрямна крива; твірна лінія; геометричні характеристики; осциляція; array of points; surface frame; guide curve; generating line; geometric characteristics; oscillation